2019
DOI: 10.1371/journal.pone.0211203
|View full text |Cite
|
Sign up to set email alerts
|

Cost minimization analysis of line probe assay for detection of multidrug-resistant tuberculosis in Arkhangelsk region of Russian Federation

Abstract: BackgroundThe development of new diagnostic tools allows for faster detection of both tuberculosis (TB) and multidrug-resistant (MDR) TB and should lead to reduced transmission by earlier initiation of anti TB therapy. The research conducted in the Arkhangelsk region of the Russian Federation in 2012–14 included economic evaluation of Line Probe Assay (LPA) implementation in MDR-TB diagnostics compared to existing culture-based diagnostics of Löwenstein Jensen (LJ) and BacTAlert. Clinical superiority of LPA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Indeed, the feasibility of rapid molecular testing on sputum samples has been associated with a median decrease in time of 25–66 days to appropriate treatment initiation in some programmatic settings [14,15]. Rapid molecular testing diagnostic algorithms have also been shown to correspond to as much as 4.5 times reduction in healthcare cost per patient when compared to phenotypic DST [16].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the feasibility of rapid molecular testing on sputum samples has been associated with a median decrease in time of 25–66 days to appropriate treatment initiation in some programmatic settings [14,15]. Rapid molecular testing diagnostic algorithms have also been shown to correspond to as much as 4.5 times reduction in healthcare cost per patient when compared to phenotypic DST [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness acceptability curves (CEACs) were included in both articles [25,26], using the net benefit regression framework [36]. The reduction in antibiotic prescriptions was expressed in monetary terms 1 (50%) [87] 2 (29%) [89,90] (33%) [98] Middle income 5 (42%) [29,[32][33][34][35] 9 (20%) [38,43,55,58,64,71,75,79,84] 0 (0%) 2 (29%) [92,94] (67%) [96,97] Low income 1 (8%) [35] 5 (11%) [38,[44][45][46]83] 0 (0%) 1 (14%) [93] (33%) [98] as additional costs per patient prescription avoided [25] or additional costs per percentage reduction in antibiotic prescriptions [26]. Nicholson et al conducted a randomised controlled trial and health-economic evaluation of diagnostic tests for influenza, respiratory syncytial virus (RSV) and Streptococcus pneumoniae in adults hospitalised for chronic or acute cardiopulmonary illness in the UK [24].…”
Section: Regression Models and Trial-based Analysesmentioning
confidence: 99%
“…Two studies presented a cost-effectiveness frontier to compare the different strategies included in the analysis [32,33]. The two studies assessing POC Xpert testing in South Africa had different conclusions compared with current care: cost saving [29] or cost effective (albeit more expensive) [31], while the study in the South African laboratory setting concluded that the higher costs were Note that not all items are reported by all articles; hence not all columns sum to the total included articles a Including a microsimulation [96] and two database studies [97,98] b According to World Bank definitions c Including sinusitis, pharyngitis, sore throat and general respiratory infections Cost-minimisation 0 (0%) 2 (4%) [54,65] 0 (0%) 0 (0%) 2 (67%) [97,98] a not matched by the improvement in TB diagnostic efficacy [34]. Wang et al concluded that the price increase related to performing a second Xpert test is relatively high [32].…”
Section: Regression Models and Trial-based Analysesmentioning
confidence: 99%
See 2 more Smart Citations